2009
DOI: 10.1055/s-0029-1211107
|View full text |Cite
|
Sign up to set email alerts
|

Short- and Long-term Effects of a Dopamine Agonist (Lisuride) on Sex-specific Behavioural Patterns in Rats

Abstract: Lisuride induces in juvenile male and especially in female rats a significant increase of the male-typical initiating activity in tests on social play-fighting behaviour. In neonatally castrated as well as in prenatally stress exposed males, castrated in adulthood, which exhibit under androgen substitution alone bisexual or even predominantly heterotypical sexual behaviour, additional treatment with lisuride resulted in a temporary normalization of sexual orientation in the homotypical male direction, limited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Neonatal administration of dopamine agonist masculinizes social play (Götz et al, 1991; Olesen et al, 2005; Tönjes et al, 1989) and males have higher dopamine content in the early postnatal period across many brain regions (Balan et al, 2000; Connell et al, 2004; Lesage et al, 1996). Although dopamine is traditionally viewed as important for the processing of rewards (Wise and Rompre, 1989), it is more broadly implicated in attention to salient events, which can either be appetitive or aversive (Berridge and Robinson, 1998; Salamone et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Neonatal administration of dopamine agonist masculinizes social play (Götz et al, 1991; Olesen et al, 2005; Tönjes et al, 1989) and males have higher dopamine content in the early postnatal period across many brain regions (Balan et al, 2000; Connell et al, 2004; Lesage et al, 1996). Although dopamine is traditionally viewed as important for the processing of rewards (Wise and Rompre, 1989), it is more broadly implicated in attention to salient events, which can either be appetitive or aversive (Berridge and Robinson, 1998; Salamone et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Male sexual behaviour can be disrupted by neonatal treatment with dopamine receptor agonists (60) and antagonists (61), as well as dopamine synthesis inhibitors (60). Furthermore, adult female sexual behaviour is defeminised after perinatal treatment with dopamine agonists (62, 63). Dopamine also appears to be important for sexual differentiation of social play behaviour.…”
Section: Neurotransmitters and Play Developmentmentioning
confidence: 99%
“…Dopamine also appears to be important for sexual differentiation of social play behaviour. Neonatal treatment of females with a dopamine receptor agonist, lisuride, masculinises the juvenile and peripubertal play behaviour (62, 63). We have recently confirmed that neonatal treatment of female rats with the dopamine D1‐like receptor agonist, SKF 38393, also masculinises juvenile social play (30).…”
Section: Neurotransmitters and Play Developmentmentioning
confidence: 99%
“…For example, neonatal treatment with dopamine antagonists and synthesis inhibitors interferes with normal masculinisation of sexual behaviour in males without altering testosterone levels (17, 18). Likewise, neonatal treatment with dopamine D1 receptor agonists appears to masculinise prepubertal social play and defeminise adult sex behaviour in females (16, 19, 20). Taken together, these data suggest that dopamine plays a role in the normal development of sexually dimorphic social play and sexual behaviour.…”
mentioning
confidence: 99%